Indian Elections 2004: A Retrospective Analysis and Overview - Surendra, Lawrence (Kasarinlan: Philippine Journal of Third World Studies; Vol 19 No 2 (2004): Electoral Politics 1, 2007)
Elections at best reflect three dimensions of formal democracy—representation in terms of representing the political will of the people; integration in terms of social classes and groups largely done through political parties, which represents the stabilising aspect of democracy; and decisions generated from stable majorities through coalitions or a single party to ensure “majorities” within parliaments and their governability. In many societies democracy can be and has been subverted in all three dimensions. Electoral results and their reflections on democracy, at best, can be tendential statements of what the results reveal.
Keywords: India; elections; liberal democracy